2020
DOI: 10.1039/d0nj00907e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of CO2to LPG over CuZnZr/MeSAPO-34 catalysts

Abstract: A synergetic relationship established between the metal and modified zeolite components favored higher selectivity for the target product (LPG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…A significant body of literature exists illustrating the advantages of thermochemical multifunctional catalysis (i.e., the combination of a metal/metal oxide and a zeolite as a multifunctional catalyst) for the hydrogenation of CO 2 to useful products. Chief among the advantages is the sheer tunability of the product distribution that can be achieved by choosing the appropriate components of the multifunctional catalyst. This has repeatedly been demonstrated in the literature with products ranging from light olefins to aromatics and paraffins being obtained by employing complementary configurations of a multifunctional catalyst.…”
Section: Introductionmentioning
confidence: 62%
“…A significant body of literature exists illustrating the advantages of thermochemical multifunctional catalysis (i.e., the combination of a metal/metal oxide and a zeolite as a multifunctional catalyst) for the hydrogenation of CO 2 to useful products. Chief among the advantages is the sheer tunability of the product distribution that can be achieved by choosing the appropriate components of the multifunctional catalyst. This has repeatedly been demonstrated in the literature with products ranging from light olefins to aromatics and paraffins being obtained by employing complementary configurations of a multifunctional catalyst.…”
Section: Introductionmentioning
confidence: 62%
“…When CIZO and SAPO-34 were in close contact, DME formation was more efficient. Tong et al [196] investigated the CO 2 hydrogenation to liquid petroleum gas (LPG) over a ternary hybrid of CuZnZr (CZZ) metal oxide and me/ SAPO-34 zeolite (me = Mn, Zn, or Zr)) where the particle mixture of both was effectively utilized. The results revealed that changing the acidity density and strength, along with altering the CZZ to me/SAPO-34 mass ratio, would have a mutually critical effect on the selectivity of LPG.…”
Section: Tri-metal and Tri-metal-oxides/sapo-34 Catalystsmentioning
confidence: 99%
“…When CIZO and SAPO‐34 were in close contact, DME formation was more efficient. Tong et al [196] . investigated the CO 2 hydrogenation to liquid petroleum gas (LPG) over a ternary hybrid of CuZnZr (CZZ) metal oxide and me/SAPO‐34 zeolite (me=Mn, Zn, or Zr)) where the particle mixture of both was effectively utilized.…”
Section: Sapo‐34 Based Catalysts For Co2 Conversionmentioning
confidence: 99%
“…Note that, in general, the catalyst components for the synthesis of hydrocarbons from СО2 are the same as for the synthesis of FT. The review [114] presents the progress achieved in recent years in the synthesis of catalysts for the hydrogenation of CO2. In C2+ hydrocarbons, the study of the mechanism of this reaction by combining experimental data and calculations based on the density functional theory (DFT), the factors influencing the performance of the catalysts are indicated, the mechanism of the formation of the C-C bond through various routes is given.…”
Section: Mechanism Of Co2 Hydrogenation To Hydrocarbonsmentioning
confidence: 99%